1995
DOI: 10.1146/annurev.ge.29.120195.003135
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Multidrug Transporter

Abstract: The analysis of how human cancers evade chemotherapy has revealed a rich variety of cell-based genetic changes resulting in drug resistance. One of the best studied of these genetic alterations is increased expression of an ATP-dependent plasma membrane transport system, known as P-glycoprotein, or the multidrug transporter. This transporter actively effluxes a large number of natural product, hydrophobic, cytotoxic drugs, including many important anticancer agents. This review focuses on the genetic and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
235
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(239 citation statements)
references
References 210 publications
(183 reference statements)
4
235
0
Order By: Relevance
“…45,46 Several MDR1 mutations have been characterized that increase resistance to other compounds. 26 Since point mutations of the MDR1 cDNA affect the substrate specificity of the multidrug transporter, it appears possible to design vectors which are particularly effective for protection of hematopoietic cells against certain drugs.…”
Section: Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 Several MDR1 mutations have been characterized that increase resistance to other compounds. 26 Since point mutations of the MDR1 cDNA affect the substrate specificity of the multidrug transporter, it appears possible to design vectors which are particularly effective for protection of hematopoietic cells against certain drugs.…”
Section: Gene Therapymentioning
confidence: 99%
“…The products of chemoresistance genes like MDR1 can be used in live organisms, unlike proteins that confer resistance to drugs like hygromycin, neomycin or puromycin because of the toxicity profile or pharmacokinetics of their respective substrates. 26 An attractive application is to coexpress drug-selectable genes with genes that correct genetically determined disorders from polycistronic cassettes or from open reading frames encoding fusion proteins. Exposure to cytotoxic drugs should enhance expression of both the chemoresistance gene and the second gene in target cells.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane proteins belonging to the ATP-binding cassette (ABC) family of transport proteins play a central role in resistance by actively decreasing the intracellular drug concentration. In humans, two members of the ABC-transporter family have been identified that can render tumour cells MDR: MDR1 P-glycoprotein (Pgp) (Gottesman et al, 1995), and the multidrug resistance protein (MRP1) .…”
mentioning
confidence: 99%
“…In this configuration, both genes are under the transcriptional control of a single strong Harvey murine sarcoma retroviral promoter, eliminating the possible negative effects which occur in retroviral vectors containing two enhancer/promoter regions, 17 and potentially allowing selection with MDR1 to produce a population of high expressing recipient cells. 11 Another similar approach which has been used is the transcriptional fusion of two genes which results in one transcription unit encoding a physical fusion of the two proteins. 18,19 However, this approach is limited to situations where a fusion construct does not interfere with the functions of each unit of the protein.…”
Section: Advantages Of Bicistronic Configuration In Retroviral Vectorsmentioning
confidence: 99%
“…The MDR1 gene is currently under investigation as a suitable selectable marker for gene therapy. 10,11 The MDR1 gene encodes an ATP driven Pglycoprotein efflux pump (Pgp) that pumps out of cells a variety of cytotoxic compounds and antitumor agents such as alkaloids, anthracyclines and epipophylotoxins. 12 The unique flexibility of this system to confer resistance to many different drugs together with reports suggesting its potential function as a selectable gene in vivo, [13][14][15] makes the MDR1 gene a good candidate to be used in gene therapy protocols.…”
Section: Introductionmentioning
confidence: 99%